'The spiral just keeps on going': Cascading health and social issues for women living and aging with HIV. (January 2022) - Herron, Lisa-Maree; Mutch, Allyson; Mugamu, Melania; Howard, Chris; Fitzgerald, Lisa
Background: There has been limited qualitative inquiry aimed at understanding the gendered and unique experiences of women living with HIV in high-income countries. In Australia, the relatively small number of women living with HIV means they have been largely overlooked in social, clinical, and policy representations of HIV over time. Objectives: To explore the experiences of women living long-term and aging with HIV, to understand the complex intersections between their health and social trajectories. Methods: Data were collected as part of Living Positive in Queensland, a longitudinal qualitative study of the experiences of living long-term and aging of people living with HIV in Queensland, Australia. This study analysed data from three annual, semi-structured interviews with the 11 female participants. Results: Women negotiated gendered roles and identities as they grappled with ongoing and intertwined health and psychosocial challenges over their life course. Development of co-morbidities, experiences of stigma, gendered social roles, financial precarity, and limited social support amplified the challenges of living with HIV and cumulatively impacted women's health and wellbeing as they aged with HIV. Conclusion: The health and wellbeing of women living with HIV are adversely impacted by intersecting complex health issues, HIV-related stigma, gendered identities, social disadvantage, and aging. Greater attention to the unique needs of women living with HIV is necessary to reduce the prevalence of psychological distress, financial stress, and vulnerability to social isolation which, in turn, lead to poorer health.